2015
DOI: 10.1007/s00192-015-2782-x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fragments on a scaffold in rats: a potential regenerative strategy in urogynecology

Abstract: In this pilot study, MPEG-PLGA scaffolds seeded with autologous MFF affected some histological and biomechanical properties of native tissue repair in an abdominal wall defect model in rats. The method thus appears to be a simple tissue engineering concept with potential relevance for native tissue repair of POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…After 8 weeks, there was a massive ingrowth of cells between and around the PCL fibers resulting in the formation of a neo-tissue/PCL construct, which was sufficiently strong to prevent hernia formation in a partial and even in a full thickness abdominal wall defect. In contrast to our previous findings with an MPEG-PLGA scaffold, 46 the present study demonstrated that the PCL scaffold seemed to be unable to function as a carrier or anchor for muscle stem cells in the form of autologous MFFs. No fluorescence-labelled or desmin-positive cells or fragments were recovered in association with the neo-tissue/PCL construct, and biomechanical testing showed no differences in parameters between scaffolds with or without MFFs.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…After 8 weeks, there was a massive ingrowth of cells between and around the PCL fibers resulting in the formation of a neo-tissue/PCL construct, which was sufficiently strong to prevent hernia formation in a partial and even in a full thickness abdominal wall defect. In contrast to our previous findings with an MPEG-PLGA scaffold, 46 the present study demonstrated that the PCL scaffold seemed to be unable to function as a carrier or anchor for muscle stem cells in the form of autologous MFFs. No fluorescence-labelled or desmin-positive cells or fragments were recovered in association with the neo-tissue/PCL construct, and biomechanical testing showed no differences in parameters between scaffolds with or without MFFs.…”
Section: Discussioncontrasting
confidence: 99%
“…Load was plotted against elongation resulting in bilinear curves with low- and high-stiffness zones. 4 To calculate stress (MPa), the initial thickness and width of the specimens were measured without squeezing the tissue. Stress was plotted against strain (relative elongation), which also resulted in bilinear curves.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this approach requires extensive in vitro cell and tissue processing, which is costly and time‐consuming. An alternative option to address the current limitations has been previously tested via implantation of muscle fibers (MFs) and bundles into the muscle defect (Collins & Zammit, ; Gras, Klarskov, & Lose, ; Hall, Banks, Chamberlain, & Olwin, ; Jango, Gras, Christensen, & Lose, ; Lecoeur et al, ). Previous studies have utilized single or multiple MFs with random distributions in size and irregular fiber orientation/organization, which were obtained by a simple mincing or enzymatic digestion process of the muscle tissue.…”
Section: Introductionmentioning
confidence: 99%